Association of colorectal carcinoma and metabolic syndrome - Josip Lesko (Medicinski glasnik, 2019)
Aim: Colorectal carcinoma is one of the most common neoplasms, especially in Western countries and those with westernisation. On the other hand, high rate of metabolic syndrome (MetSy) has also been noticed, as well as in Western countries. It seems like these two conditions are somehow connected. In this study, we wish to explore some characteristics of colorectal carcinoma and its correlation with MetSy. Methods: In this retrospective study the data were taken from medical records of 67 patients with colorectal carcinoma, and for 30 healthy controls. Input parameters of patients were compared mutually, as well as with parameters of healthy, control examinees that had negative screening colonoscopy for neoplasm. Results: Average age of patients was 68 years. The most frequent localisation of neoplasm was on rectum (53.7%) and most frequent level was Dukes C (38.8%). The patients had MetSy more frequently when compared with controls (p=0.048), and also they had more MetSy components (p=0.006). The link between MetSy and localisation of neoplasm was not found, neither with its pathohystological characteristics. Conclusion: Patients with MetSy should be warned about the increased risk of colorectal carcinoma, and, in this way, motivated for earlier and more frequent screening colonoscopies, as well as of a change of unhealthy lifestyle.
Keywords: colorectal surgery; colonoscopy; diabetes mellitus; hypertension; abdominal obesity